Introduction to Sociology - Griffiths, Heather; Keirns, Nathan; Strayer, Eric; Open Textbook Library (Open Textbook Library, 2015)
Introduction to Sociology 2e adheres to the scope and sequence of a typical, one-semester introductory sociology course. It offers comprehensive coverage of core concepts, foundational scholars, and emerging theories. The textbook presents section reviews with rich questions, discussions that help students apply their knowledge, and features that draw learners into the discipline in meaningful ways. The second edition has been updated significantly to reflect the latest research and current, relevant examples. Changes made in Introduction to Sociology 2e are described in the preface to help instructors transition to the second edition.
1 An Introduction to Sociology -- 2 Sociological Research -- 3 Culture -- 4 Society and Social Interaction -- 5 Socialization -- 6 Groups and Organization -- 7 Deviance, Crime, and Social Control -- 8 Media and Technology -- 9 Social Stratification in the United States -- 10 Global Inequality -- 11 Race and Ethnicity -- 12 Gender, Sex, and Sexuality -- 13 Aging and the Elderly -- 14 Marriage and Family -- 15 Religion -- 16 Education -- 17 Government and Politics -- 18 Work and the Economy -- 19 Health and Medicine -- 20 Population, Urbanization, and the Environment -- 21 Social Movements and Social Change
In English.
Description based on online resource
Keywords: Social sciences -- Textbooks; Sociology -- Textbooks; Religion -- Textbooks